The relationship between the young catholic movement and the soviet regime from 1940 to 1941 - Labanauskas, Ramūnas (Genocidas ir rezistencija, 2010)
This article explores the relationship between the Young Catholic Movement (hereinafter—YCM), which began operating in Lithuania in the second half of the thirties and included public and cultural figures of the intellectual Catholic elite (Pranas Dielininkaitis, Ignas Skrupskelis, Juozas Ambrazevičius, Juozas Grinius, Antanas Maceina, and others), and the Soviet regime between 1940 and 1941. In this period, the public and political Catholic elite, expecting a war between Germany and the Soviet Union soon and thinking that the Soviet regime would be short-lived, opted for an externally loyal form of cooperative relationship with the Soviet regime, at the same time making all efforts to retain the public Catholic structures that operated before the occupation. A major part of the elite secretly sought to re-establish Lithuania’s independence with the help of Germany, whereas others were more cautious about the German orientation and did not reject dependence on the USSR as a more handy option for the Lithuanian nation. One of the latter was Rev. Mykolas Krupavičius, who most actively advised the new government to cooperate with the Soviets in the summer of 1940. However, the episcopate’s modus vivendi with the regime was two-faced—pretended loyalty while at the same time secretly acting against the regime.